Powinności w perspektywie pojęć niedookreślonych - Bogucka, Izabela (Kwartalnik Prawa Publicznego, 2016)
The text contains analysis of normative and axiological basis concerning associations, especially – sports clubs operating in the form of associations as a point of reference to the conclusions regarding the activities of public administration. The main subject is how to define the concept of freedom of association and what principles does it include.